2006
DOI: 10.1542/peds.2006-0116
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Perinatal Outcomes and Risk for Postpartum Suicide Attempt in Washington State, 1987–2001

Abstract: Maternal complications were not associated with hospitalizations for suicide attempts in the year after delivery. However, fetal death or the death of an infant in the first year after delivery was strongly associated with hospitalization for a suicide attempt. These risk factors may be useful predictors for health care providers who care for women or children during the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 19 publications
11
39
0
Order By: Relevance
“…The majority of women in the current sample had attempted suicide using violent methods, confirming earlier reports of high rates of dramatic methods of suicide, with high intentionality [2,4]. Earlier studies have also shown that in the general population, Axis 1 disorders, particularly depressive disorders and substance use disorders, are important predictors of suicidality [18,19].…”
Section: Discussionsupporting
confidence: 86%
“…The majority of women in the current sample had attempted suicide using violent methods, confirming earlier reports of high rates of dramatic methods of suicide, with high intentionality [2,4]. Earlier studies have also shown that in the general population, Axis 1 disorders, particularly depressive disorders and substance use disorders, are important predictors of suicidality [18,19].…”
Section: Discussionsupporting
confidence: 86%
“…57 In this study, labor and delivery complications, cesarean section, pre-term delivery, low birthweight, and congenital malformations were not associated with increased risk of suicide attempts. A review of studies that confirmed that suicide rates are lower during pregnancy and the postpartum period emphasized that perinatal women complete suicide by more violent and lethal means than do women who are not perinatal.…”
Section: Ppdmentioning
confidence: 48%
“…Previous studies, mainly in developed countries showed that suicide is the leading cause [5] or within the leading causes [8,11] of maternal deaths in some countries. Few developing countries also documented suicide as a leading cause among high risk groups [12].…”
Section: Discussionmentioning
confidence: 99%
“…Few developing countries also documented suicide as a leading cause among high risk groups [12]. However, it has been traditionally considered as an indirect cause [3,8,9,11,12] of maternal death and even in some developed countries, deaths due to suicide are not included in the maternal mortality investigation system.…”
Section: Discussionmentioning
confidence: 99%